Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

what does 2(n-3)=4n+1 equal

Sagot :

Answer:

n=4/-3

Step-by-step explanation:

2n-3 = 5n+1

2n-5n = 1+3

-3n = 4

n =4/-3

n=-4/3

ANSWER

2(n-3) = 4n+1

(2×n) + (2×-3) = 4n+1

2n + (-6) = 4n + 1

2n - 6 = 4n + 1

2n - 6+6 = 4n + 1 + 6

2n = 4n + 7

2n - 4n = 4n - 4n + 7

-2n = 7

-2n/-2 = 7/-2

n = -3 1/2